Resorbable Synthetic Ventral Hernia Repair in Contaminated Fields: Outcomes with Poly-4-Hydroxybutyrate Mesh. Issue 6 (26th October 2021) - Christopher, Adrienne N.; Morris, Martin P.; Jia, Hanna; Broach, Robyn; Fischer, John P.
Abstract : Background: Hernia repair in the setting of contamination poses unique challenges, including complications such as recurrence and mesh infection. The ideal contaminated hernia repair including type of mesh use remains controversial. Poly-4-hydroxybutyrate is a biosynthetic scaffold for soft-tissue reinforcement and hernia repair and is potentially useful in contaminated hernia repair. The authors aim to describe postoperative outcomes, recurrence, and patient-reported outcomes after contaminated hernia repair with poly-4-hydroxybutyrate. Methods: Adult patients (≥18 years) undergoing a contaminated hernia repair with poly-4-hydroxybutyrate (Phasix) performed by a single plastic surgeon between January of 2015 and May of 2020 were identified. Patients with a ventral hernia defect and a Centers for Disease Control and Prevention wound class of II, III, or IV were included. Primary outcomes included recurrence, surgical-site infection, surgical-site occurrences, and surgical-site infection/occurrences requiring procedural interventions. As a secondary outcome, the authors assessed patient-reported outcomes as defined by the Abdominal Hernia-Q and Hernia-Related Quality of Life Survey. Results: Sixty patients were included with a median age of 52.5 and body mass index of 31 kg/m 2 . Median defect size was 300 cm 2 . Twenty-eight patients (46.7 percent) experienced a complication. The most common complications were surgical-site occurrence [ n = 20 (33.3 percent)] and surgical-site infection [ n = 10 (16.7 percent)]. Median follow-up was 24.2 months, with a recurrence rate of 8.3 percent ( n = 4). Overall patient-reported outcomes improved postoperatively, and improvement was not affected by the presence of a complication. Conclusions: Poly-4-hydroxybutyrate use in contaminated hernia repair shows promising results with an acceptable safety profile. Although complications are frequent in this complex cohort, patient-reported outcomes improvement was significant even in patients with complications. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, IV.